2014
DOI: 10.1371/journal.pntd.0002633
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma cruzi Satellite DNA OligoC-TesT and Trypanosoma cruzi Kinetoplast DNA OligoC-TesT for Diagnosis of Chagas Disease: A Multi-cohort Comparative Evaluation Study

Abstract: BackgroundThe Trypanosoma cruzi satellite DNA (satDNA) OligoC-TesT is a standardised PCR format for diagnosis of Chagas disease. The sensitivity of the test is lower for discrete typing unit (DTU) TcI than for TcII-VI and the test has not been evaluated in chronic Chagas disease patients.Methodology/Principal FindingsWe developed a new prototype of the OligoC-TesT based on kinetoplast DNA (kDNA) detection. We evaluated the satDNA and kDNA OligoC-TesTs in a multi-cohort study with 187 chronic Chagas patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…Plasma was stored at 4°C until testing for specific antibodies with CATT/ T.evansi and subsequently frozen at −20°C. From the remaining blood specimen, 500 μL of buffy coat layer were collected by means of a micropipette with a filter tip and mixed with an equal volume of guanidium EDTA buffer (GEB; 6 M guanidium chloride, 0.2 M EDTA, pH 8.0) and stored at ambient temperature until DNA extraction [ 68 ]. Of those animals that were parasitologically positive, part of the buffy coat was collected for cryopreservation in liquid nitrogen for later isolation of the parasite according to Pyana et al [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plasma was stored at 4°C until testing for specific antibodies with CATT/ T.evansi and subsequently frozen at −20°C. From the remaining blood specimen, 500 μL of buffy coat layer were collected by means of a micropipette with a filter tip and mixed with an equal volume of guanidium EDTA buffer (GEB; 6 M guanidium chloride, 0.2 M EDTA, pH 8.0) and stored at ambient temperature until DNA extraction [ 68 ]. Of those animals that were parasitologically positive, part of the buffy coat was collected for cryopreservation in liquid nitrogen for later isolation of the parasite according to Pyana et al [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, data concerning PCR were extracted from 24 reports ( Avila et al 1993 , Wincker et al 1994 , 1997 , Britto et al 1995 , Espinoza et al 1996 , Junqueira et al 1996 , Carriazo et al. 1998 , Chiaramonte et al 1999 , Gomes et al 1999 , Ribeiro-dos-Santos et al 1999 , Castro et al 2002 , Gutierrez et al 2004 , Duarte et al 2006 , Gil et al 2007 , Piron et al 2007 , Fitzwater et al 2008 , Deborggraeve et al 2009 , Ferrer et al 2009, 20 , 2013 , Ramírez et al 2009 , Batista et al 2010 , Gilber et al 2013 , Sabino et al 2013) , but only one commercial test was found ( Deborggraeve et al 2009 , De Winne et al 2014) . However, the original authors modified the commercial version in two of the studies for research purposes (De Winne et al 2014) .…”
Section: Study Selectionmentioning
confidence: 99%
“…The standards for the qPCRs were generated using DNA from T. cruzi (Dm28c) epimastigotes. Considering that one parasite contains about 100 fg of DNA ( 46 ), we designed a curve with initial 2.5 ng (equivalent to 25,000 parasites with C t -mean 19) and serially diluted (1:10) until the lower limit of 2.5 fg (0.025 parasites with a C t -mean 37). The reactions were performed in a StepOne sequence detection system (Applied Biosystems, Warrington, UK) using SYBR Green PCR Master Mix (Applied Biosystems, Warrington, UK).…”
Section: Methodsmentioning
confidence: 99%